Association of Structural and Functional Cardiac Changes With Transcatheter Aortic Valve Replacement Outcomes in Patients With Aortic Stenosis - Fukui, Miho; Gupta, Aman; Abdelkarim, Islam; Sharbaugh, Michael S; Althouse, Andrew D; Elzomor, Hesham; Mulukutla, Suresh; Lee, Joon S; Schindler, John T; Gleason, Thomas G; Cavalcante, João L (JAMA cardiology, 2019)
Severe aortic stenosis causes pressure overload of the left ventricle, resulting in progressive cardiac dysfunction that can extend beyond the left ventricle. A staging system for aortic stenosis has been recently proposed that quantifies the extent of structural and functional cardiac changes in aortic stenosis. To confirm the reproducibility of a proposed staging system and expand the study findings by performing a survival analysis and to evaluate the association of aortic stenosis staging with both cardiac and noncardiac post-transcatheter aortic valve replacement (TAVR) readmissions. A cohort analysis was conducted involving patients with severe aortic stenosis who underwent TAVR at the University of Pittsburgh Medical Center between July 1, 2011, and January 31, 2017. Patients who had undergone TAVR for valve-in-valve procedures and had an incomplete or unavailable baseline echocardiogram study for review were excluded. Clinical, laboratorial, and procedural data were collected from the Society of Thoracic Surgeons database and augmented by electronic medical record review. The aortic stenosis staging system is based on echocardiographic markers of abnormal cardiac function. The stages are as follows: stage 1 (left ventricle changes - increased left ventricular mass index; early mitral inflow to early diastolic mitral annulus velocity (E/e') >14; and left ventricular ejection fraction <50%), stage 2 (left atrial or mitral changes - left atrial volume index >34 mL/m2; moderate to severe mitral regurgitation; and atrial fibrillation), stage 3 (pulmonary artery or tricuspid changes - pulmonary artery systolic pressure ≥60 mm Hg; moderate to severe tricuspid regurgitation), and stage 4 (right ventricle changes - moderate to severe right ventricle dysfunction). Primary outcome was post-TAVR all-cause mortality. Secondary outcomes were composite outcomes of all-cause mortality and post-TAVR all-cause and cardiac-cause readmissions. A total of 689 consecutive patients (351 [50.9%] were male, with a mean [SD] age of 82.4 [7.6] years) were included. The prevalence of stage 1 was 13%; stage 2, 62%; stage 3, 21%; and stage 4, 4%. Patients with higher staging had a greater burden of comorbidities as captured by the Society of Thoracic Surgeons Predicted Risk of Mortality (STS-PROM). Despite adjustment for STS-PROM, a graded association was found between aortic stenosis staging and all-cause mortality (hazard ratio [HR] stage 2 vs stage 1: 1.37 [95% CI, 0.81-2.31; P = .25]; stage 3 vs stage 1: 2.24 [95% CI, 1.28-3.92; P = .005]; and stage 4 vs stage 1: 2.83 [95% CI, 1.39-5.76; P = .004]). Stage 3 patients had higher post-TAVR readmission rates for both cardiac (HR, 1.84; 95% CI, 1.13-3.00; P = .01) and noncardiac causes. Aortic stenosis staging appears to show a strong graded association between the extent of cardiac changes and post-TAVR all-cause mortality; such staging may improve patient care, risk stratification, assessment of prognosis, and shared decision making for patients undergoing TAVR.